2020
DOI: 10.1080/09640568.2020.1835621
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and health hazards of residents domiciled around Africa’s largest landfill

Abstract: Landfills are a nuisance and an environmental feature whose siting creates uncertainty, anxiety and unrest in nearby residential neighborhoods. As such, hazards from Africa's largest Landfill in Nigeria were surveyed, considering a 3 km radius of the site. Primary data were collected across four seasons from 473 participants in neighborhoods situated within a 1, 1-2 and 2-3 km radius of the site. The research established that environmental and health hazards experienced differ significantly in space, due to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Some benefits that could bolster a sense of place come from place dependence (livelihood). According to Dada (2020), place dependence develops when a place provides features that may support specific goals and desired activities. By meeting residents' needs, the coastal area allows them to reach their goals, and they consider it superior to other places.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Some benefits that could bolster a sense of place come from place dependence (livelihood). According to Dada (2020), place dependence develops when a place provides features that may support specific goals and desired activities. By meeting residents' needs, the coastal area allows them to reach their goals, and they consider it superior to other places.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Olusosun is Africa's largest dumpsite and the fourthlargest globally (Dada, 2021). The dumpsite was initially situated on the outskirts of Lagos State, but it is now entirely within the state's center due to urban encroachment.…”
Section: The Physical Setting Of the Study Areamentioning
confidence: 99%
“…The dumpsite was initially situated on the outskirts of Lagos State, but it is now entirely within the state's center due to urban encroachment. According to Dada (2021), it covers 43 hectares of land area and is 18 meters deep (Fig. 1 and 2).…”
Section: The Physical Setting Of the Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the research by Saleh et al, 2020 ) have shown that the environmental effects of the landfill in the operation phase are less than in the construction phase. An ANP hybrid multi-criteria decision-making technique can prioritize risks or aspects based on their importance (Dada, 2021 ; Fauzey et al, 2015 ). The ANP method forms a nonlinear network or system in cases where the interdependencies are two-way.…”
Section: Introductionmentioning
confidence: 99%